2022
DOI: 10.1093/rheumatology/keac397
|View full text |Cite
|
Sign up to set email alerts
|

Preferences for preventive treatments for rheumatoid arthritis: discrete choice survey in the UK, Germany and Romania

Abstract: Objective To quantify preferences for preventive therapies for rheumatoid arthritis (RA) across three countries. Methods A web-based survey including a discrete choice experiment was administered to adults recruited via survey panels in the UK, Germany and Romania. Participants were asked to assume they were experiencing arthralgia and had a 60% chance of developing RA in the next 2 years and completed 15 choices between no t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…This study is part of a case study for the Innovative Medicines Initiative project ‘PREFER’ (Patient Preferences in Benefit-Risk Assessments during the Medical Product Lifecycle), which aimed to develop evidence-based recommendations on how and when preference studies can inform decision-making during drug development. 14 The case study protocol 27 and other results from the case study 21 have been published previously.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is part of a case study for the Innovative Medicines Initiative project ‘PREFER’ (Patient Preferences in Benefit-Risk Assessments during the Medical Product Lifecycle), which aimed to develop evidence-based recommendations on how and when preference studies can inform decision-making during drug development. 14 The case study protocol 27 and other results from the case study 21 have been published previously.…”
Section: Methodsmentioning
confidence: 99%
“…17 One study eliciting preferences for preventive treatments for RA which used profile-case best-worst scaling 18 had a relatively small sample size and did not report acceptable benefit-risk trade-offs. A small number of quantitative studies have employed discrete choice experiments (DCEs), [19][20][21] which require large sample sizes to estimate reliable models and to account for both acceptability of treatment risks and heterogeneity among preferences. Preference heterogeneity in a DCE study of 288 self-reported FDRs was not explained by participant characteristics.…”
Section: What This Study Addsmentioning
confidence: 99%
“…Health literacy and perceived risk partly explained preference heterogeneity; however, no other patient characteristics explained heterogeneity. 51 Although scale was investigated, a scaleadjusted latent class model could have been suitable for this purpose but would have further complicated sample comparisons. 52 Despite the limitations, this study provides a starting point for discussion on using the general public as a proxy in the context of disease prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Approaching RA prevention presents an ongoing challenge in rheumatology. Although early initiation of immunotherapies in at-risk individuals is encouraging, previous studies have shown that many at-risk individuals have concerns about pharmacological side effects [ 13 , 16 , 19 ]. In congruence, our findings suggest that side effects associated with the medication used to treat RA could cause concern for at-risk individuals, regardless of how proactive they might be in other ways.…”
Section: Discussionmentioning
confidence: 99%
“…There is a pressing need for further understanding of how at-risk individuals weigh up the risk of developing RA vs the benefits of preventive interventions [ 18 ]. Furthermore, determining preferences for lifestyle approaches to reduce the risk of RA development in at-risk groups has been identified as an important topic for further study [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%